Sabah women fired up to wrest crown - Xavier, Francis (New Sabah Times English (KK), 2016)
Kota Kinabalu: Powerhouse Sabah are all fired up to wrest the crown from defending champions MISC-MIFA at the 29th Tun Sharifah Rodziah Football Tournament 2016, which will be held at Universiti Utara Malaysia (UUM), Sintok in Kedah from April 7 to 16.